2022
DOI: 10.1037/vio0000422
|View full text |Cite
|
Sign up to set email alerts
|

Associations between witnessing and perpetrating online hate speech among adolescents: Testing moderation effects of moral disengagement and empathy.

Abstract: Objective: The open expression of hatred, hostility, and violence against minorities has become a common online phenomenon. Adolescents are at particular risk of being involved in different hate speech roles (e.g., witness, perpetrator). However, the correlates of their involvement as perpetrators and the mechanisms that might explain their involvement in hate speech across different roles have not yet been thoroughly investigated. To this end, this study investigates moral disengagement and empathy as correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 53 publications
6
19
0
Order By: Relevance
“…This finding is aligned with research showing that empathy is negatively related to antisocial behavior, intolerance, and prejudice (Boag & Carnelley, 2016;Pettigrew & Tropp, 2008) and positively associated with defending victims of bullying (Deng et al, 2021;Van Noorden et al, 2015). Moreover, the present study extends previous research showing that empathy is negatively related to online hate speech perpetration among adolescents (Wachs et al, 2022a(Wachs et al, , 2022b.…”
Section: Hypothesis 1: Direct Associations Between Classroom Climate ...supporting
confidence: 91%
See 1 more Smart Citation
“…This finding is aligned with research showing that empathy is negatively related to antisocial behavior, intolerance, and prejudice (Boag & Carnelley, 2016;Pettigrew & Tropp, 2008) and positively associated with defending victims of bullying (Deng et al, 2021;Van Noorden et al, 2015). Moreover, the present study extends previous research showing that empathy is negatively related to online hate speech perpetration among adolescents (Wachs et al, 2022a(Wachs et al, , 2022b.…”
Section: Hypothesis 1: Direct Associations Between Classroom Climate ...supporting
confidence: 91%
“…In contrast, meta-analyses and systematic reviews revealed that high levels of empathy are related to defending victims of bullying against students who perpetrate bullying (e.g., Deng et al, 2021 ; Van Noorden et al, 2015 ). Other empirical research on hate speech found that adolescents are less likely to be perpetrators of such behavior when they think that online hate speech leads to negative consequences ( Wachs et al, 2022a , 2022b ). What is unknown so far is whether empathy for victims of hate speech is positively associated with counterspeech among adolescents.…”
Section: A Socio-ecological Framework To Understand Counterspeech Amo...mentioning
confidence: 99%
“…It can be assumed, for example, that understanding and feeling the affective situation of hate speech victims by vicariously experiencing their emotional distress might favor benign feelings for the victims and thus increase counter-speech. This assumption is in line with burgeoning research on hate speech that revealed that higher levels of empathy were negatively associated with the perpetration and acceptance of online hate speech (Celuch et al, 2022 ; Wachs, Bilz, et al, 2022 ). Another study revealed that adolescents who can understand and share the emotions of peers who become targets of hate speech were more likely to counter hate speech in favor of the victim (Wachs et al, 2023 ).…”
Section: Introductionsupporting
confidence: 74%
“…Few researchers have explored how moral disengagement affects individual behavioral decisions as a state or personal trait. In research that investigates the moderating effect of moral disengagement, scholars found that moral disengagement can be a stimulator when destructive behaviors happen ( Wang et al, 2018 ; Wachs et al, 2022 ). Individuals who perform deviant behaviors lack a sense of guilt or shame ( Loi et al, 2015 ), which implies that morally disengaged individuals are more likely to engage in destructive actions without scruple.…”
Section: Introductionmentioning
confidence: 99%